Prevalence and associated phenotypes of DUSP6, IL17RD and SPRY4 variants in a large Chinese cohort with isolated hypogonadotropic hypogonadism. Issue 1 (10th May 2020) - Men, Meichao; Wang, Xinying; Wu, Jiayu; Zeng, Wang; Jiang, Fang; Zheng, Ruizhi; Li, Jia-Da
Abstract : Background: FGF8-FGFR1 signalling is involved in multiple biological processes, while impairment of this signalling is one of the main reasons for isolated hypogonadotropic hypogonadism (IHH). Recently, several negative modulators of FGF8-FGFR1 signalling were also found to be involved in IHH, including DUSP6, IL17RD, SPRY2 and SPRY4 . The aim of this study was to investigate the genotypic and phenotypic spectra of these genes in a large cohort of Chinese patients with IHH. Methods: A total of 196 patients with IHH were enrolled in this study. Whole-exome sequencing was performed to identify variants, which was verified by PCR and Sanger sequencing. Results: Four heterozygous DUSP6 variants (p.S157I, p.R83Q, p.P188L and p.N355I) were found in six patients. Cryptorchidism, dental agenesis, syndactyly and blue colour blindness were commonly observed in patients with DUSP6 mutations. Six heterozygous IL17RD variants (p.P191L, p.G35V, p.S671L, p.A221T, p.I329M and p.I329V) were found in seven patients. Segregation analysis indicated that 100% (5/5) of probands inherited the IL17RD variants from their unaffected parents, and oligogenicity was found in 4/7 patients. One rare SPRY4 variant (p.T68S) was found in a female patient with Kallmann syndrome who also carried a PLXNA1 mutation. Conclusion: Our study greatly enriched the genotypic and phenotypic spectra of DUSP6, IL17RD and SPRY4 in IHH. Mutations in DUSP6 alone seem sufficient to cause IHH in an autosomal dominant manner, whereas IL17RD or SPRY4 mutations may cause IHH phenotypes in synergy with variants in other IHH-associated genes.